Motivation of foreign investment - Gutkevych, Svitlana (My University, 2012)
World experience shows that foreign investment has advantages over other forms of financing industries. For the efficiency of foreign investment necessary study.
Keywords: зарубежные инвесторы; foreign investors; зарубіжні інвестори; иностранные инвестиции; зарубежные экономические действия; резидентский для страны экспортер; получатель; импортер; кредит; портфельная инвестиция; foreign investment; foreign economic operations; investment resources; country-resident exporter; recipient; importer; loans; credit; direct investment; portfolio investment; іноземні інвестиції; зарубіжні економічні дії; інвестиційні ресурси; резидентний для країни експортер; одержувач; імпортер; позики; кредит; безпересадочні інвестиції; портфельна інвестиція; кафедра міжнародної економіки